2020
DOI: 10.1111/apa.15463
|View full text |Cite
|
Sign up to set email alerts
|

Limited agreement between clinical assessment of infant colour at birth and oxygen saturation in a hospital in Ethiopia

Abstract: The International Guidelines for Neonatal Resuscitation recommend the assessment of heart rate, breathing and oxygenation to guide the resuscitation intervention. 1,2 Since 2010, pulse oximetry has replaced infant colour as measure of oxygenation in resuscitation guidelines because the latter has been shown to be an unreliable indicator of oxygen saturation. 1-3 However, the evaluation of infant colour remains the most used indicator of oxygenation in middle-and low-resource settings where pulse oximetry is of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Our data also suggested a large underestimation of hypoxia during transport, since most desaturated infants at admission to the referral hospital had not received supplemental oxygen before. Clinical evaluation of cyanosis can be difficult as there is limited agreement between infant color and oxygen saturation, hence a pulse oximeter should be included in the ambulance equipment [20]. These problems occurred despite the frequent presence of a nurse during the transport, which was higher compared to previous studies in low/ middle-income countries [9,21,22].…”
Section: Discussionmentioning
confidence: 98%
“…Our data also suggested a large underestimation of hypoxia during transport, since most desaturated infants at admission to the referral hospital had not received supplemental oxygen before. Clinical evaluation of cyanosis can be difficult as there is limited agreement between infant color and oxygen saturation, hence a pulse oximeter should be included in the ambulance equipment [20]. These problems occurred despite the frequent presence of a nurse during the transport, which was higher compared to previous studies in low/ middle-income countries [9,21,22].…”
Section: Discussionmentioning
confidence: 98%
“…These findings suggest that SpO 2 measurement would be considered also in low-resource settings because the agreement between the assessment of infant colour and SpO 2 is limited. 32 The questions regarding supplemental oxygen still remain: oxygen or not, when and how much? Our results raise the question if these neonates would benefit from supplemental O 2 during PPV.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, preventing dangerous hyperoxia is also recommended3 4 7; of note, 33% of neonates receiving supplemental oxygen after PPV had SpO 2 levels above target range (>95%) at 10 min. These findings suggest that SpO 2 measurement would be considered also in low-resource settings because the agreement between the assessment of infant colour and SpO 2 is limited 32…”
Section: Discussionmentioning
confidence: 99%
“…6 Systematic reviews have shown that this programme changes newborn resuscitation practices at health facilities in low-resource settings. 7 In this issue of Acta Paediatrica, Cavallin et al 8 analyse one step in the initial management of newborn babies in a low-income setting: the clinical assessment of the neonate's colour at birth. They looked at how closely the cyanotic or pink colour that is observed in newborn infants corresponded to levels of pulse-oximeter data at 1.0, 1.5, 2.0 and 5.0 minutes after birth.…”
Section: Global Investment Is Needed So That Countries Can Reduce Neo...mentioning
confidence: 99%